The Effect of Work Experience, Independence, and Professional Skepticism on Auditor’s Ability to Detect Fraud at Public Accountant Firm in Bali - Putu Ayu Kartika Pratiwi; Ida Bagus Anom Yasa; I M Sumartana (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
An auditor in carrying out the audit process of financial statements requires good fraud detection capabilities so that the auditor can provide reasonable assurance that the financial statements are free from material misstatement caused by fraud. The auditor's ability to detect fraud is influenced by various factors including work experience, independence and professional skepticism. This study aims to analyze the effect of work experience, independence and professional skepticism on the auditor's ability to detect fraud. The population in this study is all auditors who work at Public Accountant Firms in Bali registered in the IAPI directory in 2020. The number of samples used is 136 auditors determined based on the saturated sample or census method. Analysis technique used in this study is a modeling technique with Partial Least Square (PLS) through the Smart PLS 3.0 application. The results showed that work experience, independence and professional skepticism had a positive and significant effect on the auditor's ability to detect fraud.